The Role of Access to Agribusiness Microfinance Institutions (LKM-A) on Poverty Reduction: Case Study in Kuningan District (Jurnal Bina Praja, 2023)
This study aims to determine whether the role of the Agribusiness Microfinance Institution (LKM-A) has an actual or significant effect on the poverty of farmer households. By using various financial instruments, especially Indonesia's aspirations towards an inclusive financial system for everyone, especially in the agricultural sector, it is very important to examine the agribusiness microfinance institutions (LKM-A) to see how much impact they have on farming communities so they can get out of poverty status. This study used a mixed method with a sample using a purposive sampling method with a total sample of 52 divided into three growing seasons (MT I, MT-II, and MT III). The analytical method used the logit or logistic regression method with the variable of interest, namely access to LKM-A debtors and ten other control variables, which are divided into financing characteristics indicators, farming characteristics indicators, and household characteristics indicators as well as qualitative findings from field interviews with respondents. The results showed that 4 out of 11 variables have a negative effect (coefficient below 1), which means that they have a relationship to reduce the risk of being poor, namely the variable access to LKMA debtors, Bank debtor access; land area, and marital status. The results of this study showed that banks have a significant effect on reducing the risk of possible poverty levels, so the government needs to provide convenience for vulnerable people, especially farmers, to be able to access LKM-A and banks and increase financial inclusion.
Keywords: Microfinance Institutions; poverty; financial inclusiveness